Study of Epstein - Barr virus Infection in Relation to the Immunohistochemical Expression of Bcl-2 gene in Tissues of Patients with Adenocarcinoma of the Colon - Sarmad M. Zeiny; Saad Hasan Mohammed Ali; Jabbar R. Zangoor; Shakir H .Mohammed Al-Alwany (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: EBV infection in tissue micro-environment is challenged by the precisely regulated survivaland apoptosis mechanisms. Abnormal bcl-2 proto-oncogene expression in colonic carcinomas allowsaccumulation and propagation of these genetically altered cells.Objective: To analyze the relevant concordance of BCL-2 gene , EBNA1 s and LMP-1-EBV expression inissues from a group of Iraqi patients with colonic adenocarcinomas.Patients and Methods: One hundred (100) tissue biopsies, belonged to (40) patients with colorectalcancers, (40) patients with benign colon tumors, and (20) apparently normal colorectal control tissues,were enrolled in this study. The detection of EBNA1 s and LMP-1-EBV as well as BCL-2 was done byimmunohistochemistry (IHC).Results: The positive-IHC results of EBNA1 detection in 40 tissues with malignant colonic tumors were57.5%, while in 40 colonic benign tumors tissues were 32.5 %. In those apparently healthy colonic controltissues, EBNA1 detection was 20%. The positive results of LMP-1 –EBV -IHC detection where 45 % fromcolonic carcinoma group, while the percentage of benign colonic tumors was 30%(12 out of 40). Lastly, inAHC was15% showed positive signals. Malignant colonic tumors showed 47.5% positive results of Bcl2-IHC detection while benign colonic tumor tissues showed 40% positive bcl-2-IHC reactions and in thecolonic control tissues was 20%.Conclusion: It concluded from the present high rates of EBV infection in colonic adenocarcinoma alongwith the concordance bcl-2 expression that they could played an important role in the development andprogression of both malignant and benign colonic tumors in our group of Iraqi patients.